The experiences of hospitalized patients during the covid-19: integrative review - Rosas Rodrigues, Cátia (2021)
Background: COVID-19 brought changes in hospital dynamics and, consequently, the need to train health professionals. Patients as vulnerable beings, during the pandemic, go through different experiences related to a new virus. Objectives: to know the scientific evidence about the emotions experienced by patients during hospitalization, throughout the COVID-19 pandemic. Methodology: an integrative literature review study using EBSCO's databases, using the MeSh keywords "patients", "emotion" and "COVID-19". Results: 9 articles were analyzed and the data from the experiences presented were organized into 5 categories: emotions, behavior, feeling, coping process and belief. Adding dimensions where the nurse can facilitate the patient's experience during hospitalization. Conclusion: nurses have a fundamental role in holistic care and work as facilitators in the patients' health-disease transition process, promoting their development and training with coping strategies for better emotions management.